Adoption of Financial Technology Innovation and Its Effect on SME Accounting Performance - Yasmine Othmani (Journal of Business Innovation and Accounting Research, 2024)
The rapid advancement of financial technology (FinTech) has emerged as a transformative force for Small and Medium Enterprises (SMEs) globally, yet its adoption and impact on accounting performance in developing economies such as Algeria remain insufficiently explored. This study investigates the determinants of FinTech adoption among Algerian SMEs and examines its subsequent effects on accounting performance metrics. Employing a quantitative research methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, data were collected from 285 SME owners and managers across multiple provinces in Algeria. The findings reveal that perceived usefulness, organizational readiness, and government support significantly influence FinTech adoption, which in turn positively affects accounting performance indicators including financial reporting quality, transaction efficiency, and decision-making capabilities. The study contributes to the limited literature on FinTech adoption in North African contexts and provides practical implications for policymakers and SME practitioners seeking to leverage technological innovations for enhanced financial management.